TEMPORARILY REACTIVE POLYELECTROLYTES TO IMPROVE LONG TERM CELL ENCAPSULATION - Gardner, Casandra M. (My University, 2012)
Coated calcium-alginate beads are the basis of many encapsulation methods used in pursuit of cell-based enzyme and hormone replacement therapies. The standard alginate - poly-L-lysine - alginate (APA) capsules consist of a calcium-alginate hydrogel core containing cells designed to express a therapeutic product, coated with permeability controlling poly-L-lysine (PLL, a polycation) followed by an exterior layer of polyanionic alginate. Although this approach is promising, the required long-term survival of the implanted cells has remained largely elusive as the current APA capsules suffer from several biocompatibility and mechanical strength issues, one of which is the weakening of ionic crosslinks over time, exposing the encapsulated cells to the host.
This thesis aims to replace the exterior layer of alginate with a Temporarily Reactive Polyelectrolyte (TPR) to reinforce AP capsules by forming covalently crosslinked shells. TRPs are polyanions that possess reactive electrophilic groups capable of forming permanent covalent crosslinks with the underlying polyamine (such as PLL), and subsequently hydrolyze, increasing the net negative charge of the polyanion. TRPs are thought to improve the biocompatibility and strength of the microcapsules by forming stable inert amide bonds, as well as increasing the net negative charge of the capsule through the liberation of carboxylates. This thesis will focus primarily on two TRPs: 50% hydrolyzed poly(methyl vinyl ether-alt-maleic anhydride), PMM50 , and poly(methacrylic acid-co-2-vinyl-4,4-dimethylazlactone) with a 50:50 co-monomer ratio, PMV50 . Their synthesis, rates of hydrolysis and capsule formation around encapsulated C2C12 cells for in-vitro and in-vivo studies will be described. Additionally the synthesis and rates of hydrolysis of other 2-vinyl-4,4-dimethylazlactone (VDMA)-copolymers are presented as potential candidates for future TRPs.
Keywords: cell encapsulation; polyelectrolyte; immunoisolation; polymerization kinetics; biomaterial; hydrogel; Biomaterials; Polymer Science; Biomaterials